2017
DOI: 10.1016/j.bbadis.2017.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine slows down oligomerisation of α-synuclein and ameliorates cytotoxicity in a yeast model of Parkinson's disease

Abstract: Several retrospective epidemiological reports have indicated an inverse correlation between smoking and development of Parkinson's disease (PD). This has mostly been attributed to the neuroprotective role of nicotine in stimulating nicotinic acetylcholine receptors and dopaminergic neurons which are damaged in PD. One of the characteristic features of PD is the intraneuronal deposition of globular inclusions of the intrinsically disordered protein α-synuclein as Lewy bodies. Using in vitro and the well-validat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 56 publications
2
34
0
Order By: Relevance
“…SNCG expression is normally restricted to the brain and peripheral neuronal tissues [14], and its aberrant expression in tissues other than those of the neuronal system is highly associated with human malignancy. Previous studies have reported that nicotine acting on brain nAChRs may affect SNCA aggregation, resulting in neuroprotection [15][16][17]. Recently, we reported that SNCG is abnormally expressed in OSCC and that its expression is strongly correlated with disease progression [2].…”
Section: Introductionmentioning
confidence: 93%
“…SNCG expression is normally restricted to the brain and peripheral neuronal tissues [14], and its aberrant expression in tissues other than those of the neuronal system is highly associated with human malignancy. Previous studies have reported that nicotine acting on brain nAChRs may affect SNCA aggregation, resulting in neuroprotection [15][16][17]. Recently, we reported that SNCG is abnormally expressed in OSCC and that its expression is strongly correlated with disease progression [2].…”
Section: Introductionmentioning
confidence: 93%
“…Among the compounds with a possible clinical application, dopaminergic agonists were found to directly affect aggregation in a Drosophila melanogaster model of α‐syn accumulation . In line with epidemiological evidence supporting that cigarette smoking lowers the risk of PD, nicotine, the main tobacco component has been found to display antifibrillogenic properties by inhibiting de novo α‐syn oligomerization and fibril formation and destabilizing preformed α‐syn fibrils in yeast . Other molecules, including psychostimulants with amphetamine‐like structure, as cocaine or methylphenidate, have been found to interact with α‐syn with differential modalities, involving either the sole N‐terminal portion or a contemporaneous N‐ and C‐terminal binding, which stabilize a neurotoxic and neuroprotective protein conformation, respectively .…”
Section: The Possible Approaches To Directly Target α‐Syn Pathologymentioning
confidence: 86%
“…31 In line with epidemiological evidence supporting that cigarette smoking lowers the risk of PD, 32 nicotine, the main tobacco component has been found to display antifibrillogenic properties by inhibiting de novo α-syn oligomerization and fibril formation and destabilizing preformed α-syn fibrils in yeast. 33,34 Other molecules, including psychostimulants with amphetamine-like structure, as cocaine or methylphenidate, have been found to interact with α-syn with differential modalities, involving either the sole Nterminal portion or a contemporaneous N-and C-terminal binding, which stabilize a neurotoxic and neuroprotective protein conformation, respectively. 35 As the central region of α-syn (aa 61-95) is most important for the conformational shift of the protein to β-sheets, numerous small molecule inhibitors of α-syn aggregation were identified, thanks to in vitro assays as ligands of residues 69-72.…”
Section: The Possible Approaches To Directly Target α-Syn Pathologymentioning
confidence: 99%
“…On the contrary, Ikeda et al observed that smoking diminish the chances of cognitive impairment and the risk for dementia [15]. In addition, Kardani et al proposed that the presence of nicotine in cigarettes activates the nicotinic acetylcholine receptors and stimulates its neuroprotective role and dopaminergic effect [16].…”
Section: Discussionmentioning
confidence: 99%